Determination of Total Phenolic Content in Muntingia Calabura L. Extract and Antioxidant Activity Test Using the Ferric Reducing Antioxidant Power Method - Palupi, Ajeng Sekar; Hidayatullah, Muhammad Haqqi (Newinera Publisher, 2024)
Natural antioxidants can be obtained from fruit, vegetables and plants, because they contain the largest compounds, namely phenolic compounds. Phenolic compounds are the largest group of compounds that function as natural antioxidants in plants. One plant that contains a lot of antioxidants is found in the cherry plant (Muntingia calabura L.). This study aims to determine the total phenolic content and antioxidant activity of the maceration and ultrasonic extraction methods of ethanol extract, ethyl acetate of cherry leaves (Muntingia calabura L.). Extraction of cherry leaves was carried out using maceration and ultrasonic methods using ethyl acetate solvent. The thick ethyl acetate and ethanol extracts of cherry leaves were measured for total phenolic content and antioxidant activity. The results of maceration extraction with ethanol solvent had a content of 58.498 mgGAE/g and ethyl acetate had a content of 58.820 mgGAE/g. The results of ultrasonic extraction with ethanol solvent had a content of 56.118 mgGAE/g and ethyl acetate had a content of 51.463 mgGAE/g. The total phenolic content of ethanol and ethyl acetate extracts of cherry leaves from the maceration and ultrasonic methods had significant differences. Ethanol and ethyl acetate extracts of cherry leaves using the maceration extraction method had antioxidant activity levels of 36,639 ppm and 39,361 ppm, while the ultrasonic method had antioxidant activity levels of 35,268 ppm and 39,179 ppm respectively. The antioxidant activity of ethanol and ethyl acetate extracts of cherry leaves from maceration and ultrasonic extraction methods has significant differences.